Metode Pembina Dalam Memberikan Bimbingan Penyesuaian Diri Terhadap Santri Baru Di Pondok Pesantren Yuhana Four Dalle Desa Tanakaraeng Kecamatan Manuju Kabupaten Gowa - Fitria Reski Ananda; Andi Abdul Hamzah; St. Rahmatiah (Danudirja Setyabudi Nusantara, 2026)
The transition from a home environment to a boarding school environment requires new students to adapt to various aspects of life, ranging from strict rules and limited social interaction with family to a busy daily routine. This adaptation process presents a unique, multidimensional challenge that requires systematic intervention from mentors. This study aims to explain the methods used by mentors to provide guidance on adjustment for new students at the Yuhana Four Dalle Islamic Boarding School in Manuju Subdistrict, Gowa Regency. The research design is descriptive qualitative, employing approaches from da’wah, communication, and psychology. Data were collected through observation, in-depth interviews, and documentation involving mentors and students. The data analysis technique adopted the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the methods used by instructors to guide new students in adjusting to their new environment include: (1) building communication through “sharing time,” (2) individual counseling, (3) habit formation and extracurricular activities, (4) setting a good example (uswatun hasanah), (5) providing advice, and (6) administering discipline or tazkirah. These six methods are applied in an integrated manner while upholding religious values, and are carried out from when students wake up until they go back to sleep. This study offers a novel perspective by exploring the mentor's role as a key figure in students’ daily lives, rather than merely as a formal counselor. The practical implications of this study are that it contributes to the development of a more effective and contextually appropriate guidance model aligned with the characteristics of traditional Islamic boarding schools.